2022
DOI: 10.1002/jcla.24808
|View full text |Cite
|
Sign up to set email alerts
|

Hematological characteristics of COVID‐19 patients with fever infected by the Omicron variant in Shanghai: A retrospective cohort study in China

Abstract: Background A wave of the Omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection has rapidly spread in Shanghai, China. Hematological abnormalities have been reported in coronavirus disease 2019 (COVID‐19) patients; however, the difference in hematological parameters between COVID‐19 patients with fever and patients who are febrile from other causes remains unexplored. Methods This retrospective cohort study enrolled 663 SARS‐CoV‐2 positive patients identified by RT‐PCR. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
(91 reference statements)
3
5
0
Order By: Relevance
“…Furthermore, the ROC curve analysis in the present study observed that a decreased levels of LYM counts (0.738) on admission might be the most valuable hematological parameter for early diagnosis of COVID-19 with fever, followed by the decreased NEU counts (0.718), increased MLR (0.713), increased PLR (0.702), decreased WBC counts (0.700), and decreased MCHC (0.687), which is in concordance with previous report [ 38 ]. These are accessible and affordable hematological parameters that may assist clinicians in making timely differential diagnoses between COVID-19 patients and non-COVID-19 patients with fever.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Furthermore, the ROC curve analysis in the present study observed that a decreased levels of LYM counts (0.738) on admission might be the most valuable hematological parameter for early diagnosis of COVID-19 with fever, followed by the decreased NEU counts (0.718), increased MLR (0.713), increased PLR (0.702), decreased WBC counts (0.700), and decreased MCHC (0.687), which is in concordance with previous report [ 38 ]. These are accessible and affordable hematological parameters that may assist clinicians in making timely differential diagnoses between COVID-19 patients and non-COVID-19 patients with fever.…”
Section: Discussionsupporting
confidence: 93%
“…It may be due to the toxicity of Omicron was attenuated compared with that of the original strain and other mutants. Additionally, the weakened immune status of pneumonia patients and the suppressed inflammatory response, consistent with earlier publications [ 38 , 52 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations